Multicenter Study of Secukinumab Survival and Safety in Spondyloarthritis and Psoriatic Arthritis: SEcukinumab in Cantabria and ASTURias Study - Alonso, Sara; Villa, Ignacio; Fernández, Sabela; Martín, José L.; Charca, Lilyan; Pino, Marina; Riancho, Leyre; Morante, Isla; Santos, Monserrat; Brandy, Anahy; Aurrecoechea, Elena; Carmona, Loreto; et al. (Frontiers in Medicine, 2021)
Objectives: We aimed to evaluate the drug retention rate and safety of secukinumab (SEC) in patients with axial spondyloarthritis (AxSpA) and psoriatic arthritis (PsA) in a real clinical setting. Methods: This multicenter retrospective observational study included all AxSpA and PsA patients who received at least one dose of SEC. Adverse events (AE) and the drug retention rate were the main study outcomes. Drug survival was analyzed by Kaplan-Meier curves while predictive factors of discontinuation were evaluated using a Cox regression analysis. The weight of these associations was estimated by hazard ratio (HR) values. Results: We included 154 patients (59 PsA and 95 AxSpA). Mean disease duration was 6.5 years (IQR 2-8). Sixty-one percent of patients were treated with two or more biologics prior to SEC. The 1 and 2-year retention rates for SEC were 66 and 43%, respectively. The main causes of discontinuation were inefficacy (59%) and AE (36%). The factors associated with lower risk of discontinuation were male gender (HR 0.54, 95% CI 0.38-0.78 p = 0.001), obesity (HR 0.53, 95% CI 0.30-0.93 p = 0.027), hypertension (HR 0.55, 95% CI 0.30-0.93 p = 0.008), and diabetes (HR 0.42 95% CI 0.18-0.99 p = 0.047) while number of previous biologics and depression were predictors of discontinuation (HR 1.18, 95% CI 1.04-1.34 p = 0.011 and HR 2.53, 95% CI 1.61-3.96 p < 0.001). Conclusions: SEC showed a good retention rate in a population previously exposed to several biological therapies. As a novelty, cardiometabolic comorbidities were associated with better drug survival.